Engineered macrophage nanoparticles enhance microwave ablation efficacy in osteosarcoma via targeting the CD47-SIRPα Axis: A novel Biomimetic immunotherapeutic approach - Xiongfa Ji; Xin Qian; Guowen Luo; Wenjie Yang; Wenhan Huang; Zehua Lei; Jiaqi Zhou; Guoqing Zhong; Jielong Zhou; Nan Liu; Limin Ma; Mei Li; et al. (Bioactive Materials)
Osteosarcoma (OS) is a lethal bone tumor that primarily affects adolescents. OS is characterized by a high incidence of recurrence following surgical intervention, which is attributed to the presence of residual microscopic disease. Tumor-associated macrophages, which dominate the tumor microenvironment, often suppress immune responses and facilitate tumor progression and recurrence. This study developed an innovative nanotherapeutic approach by utilizing genetically engineered macrophage membranes with M1 polarization, stably overexpressing signal regulatory protein alpha (SIRPα), to encapsulate microwave-responsive nano-Prussian blue (SIRPα-M@nanoPB) nanoparticles. These nanoparticles induce tumor cell death selectively through hyperthermia and microwave dynamic effects upon targeted microwave irradiation. It is of critical importance to note that the enhancement of SIRPα on the nanoparticle surface actively targets and binds CD47 of tumor cells, thereby disrupting the ''don't-eat-me'' signal and effectively countering the immunosuppressive tumor environment. This action restores macrophage phagocytosis with M1 polarization, triggering potent immune responses. Our strategy holds considerable promise when it comes to improving the efficacy of microwave ablation through immune modulation, while reducing thermal damage to adjacent normal tissue and minimizing the risk of tumor recurrence. Thus, it offers a significant advancement in microwave therapies for patients with OS.